Mode action prediction of catechin from Uncaria gambir Roxb. against UDP-N-acetylenolpyruvyl-glucosamine reductase (MurB enzyme) of Streptococcus mutans: In silico study - Hendra Dian Adhita Dharsono; Lydiawati Wibisono; Ayu Trisna Hayati; Eti Apriyanti; Mieke Hemiawati Satari; Dikdik Kurnia (Wolters Kluwer Medknow Publications, 2022)
The prevalence of oral health problems in the global population is still high, especially dental caries, which is considered a multifactorial disease involving the role of bacteria, namely Streptococcus mutans. Gram-positive bacteria metabolize carbohydrates and sugars and convert them into lactic acid, causing dental caries. The peptidoglycan (PG) layer at the outer surface of the bacteria acts as protection. MurB enzyme is known for its contribution to PG biosynthesis. Gambir (Uncaria gambir Roxb.) is famous for many efficacies. Previous studies show that catechin from herb plants such as U. gambir has antibacterial activity. This study aimed to evaluate and predict the antibacterial activity of catechin from U. gambir against the MurB enzyme, which contributes to forming the bacteria PG, with an in silico approach. The structure of the MurB enzyme was collected from UniProt, and the ligands (catechin and chlorhexidine) structures were obtained from PubChem. The AutoDock software was used to dock both ligand and MurB enzyme visualized using PyMOL and analyzed using BIOVIA. The results showed that catechin has a binding affinity of more than − 7 kcal/mol against the MurB enzyme, and chlorhexidine has a higher binding affinity than catechin. Both catechin and chlorhexidine have similar amino acids attachment by hydrogen bonds. The results showed that catechin has competitive antibacterial activity against chlorhexidine in inhibiting the MurB enzyme.